High-sensitivity magnetoresistive sensor with optimized orthogonal exchange bias for low-field measurement - Yang, Yi; Lamichhane, Suvechhya; Chen, Chun-Yen; Sokolov, Andrei; Yin, Xiaolu; Liu, Yen-Fu; Hong, Jhen-Yong; Chang, Liang-Juan; Liou, Sy-Hwang (IEEE transactions on magnetics, 2025)
An MTJ-based magnetoresistive sensor that combines optimized orthogonal exchange bias with a previously proposed magnetic flux guiding structure is studied for improved overall performance. Due to the orthogonal exchange bias, the magnetoresistive sensor exhibits reduced hysteresis, which results in improved reversibility and linearity. On the other hand, high sensitivity is still achievable owing to the magnetic flux guiding structure and double staged magnetic flux concentrators (MFC). At room temperature, with double staged MFCs, the sensitivity of the studied sensor is as high as 4.66×10 4 %/mT at zero field, and the detectivity is about 23 pT/Hz 1/2 at 1 Hz and about 2.3 pT/Hz 1/2 at 100 Hz. The improved overall performance demonstrates great potential for application of the studied sensor in low-field measurement with high sensitivity at room temperature.